COMBINATION OF BAGHDADIYAH AND ADZ-DZIKRA MEDIA IN ARABIC LEARNING MEDIA AT SDPT ULUL ABSHOR SEMARANG - Sulaiman, Agus; Al Anshory, Abdul Muntaqim; Hasaniyah, Nur; Hasyim, Muhammad (Abjadia : International Journal of Education, 2024)
This study aims to determine the effectiveness of the use of a combination of Baghdadiyah and Adz-Dzikra media in Arabic language learning at SDPT Ulul Abshor Semarang. Baghdadiyah media is used to help students recognize and understand the shape and pronunciation of Arabic letters, while Adz-Dzikra media facilitates students to practice writing Arabic letters, words, and sentences directly. The research method used is a case study with a qualitative approach. Data were collected through observation, interviews, and documentation during the Arabic language learning process at SDPT Ulul Abshor. Data analysis was carried out descriptively to identify the benefits and impacts of using the combination of media. The results of the study showed that the use of a combination of Baghdadiyah and Adz-Dzikra media proved to be effective in increasing the effectiveness of learning, as well as the ability to read and write Arabic sentences in students. Students are not only able to recognize Arabic letters, but also can compose and write simple sentences properly and correctly. In addition, the use of this combination of media also increases students' enthusiasm and motivation to learn Arabic. Based on the results of the study, it was concluded that the combination of Baghdadiyah and Adz-Dzikra media can be optimally utilized to improve the quality of Arabic language teaching at the elementary school level. Schools and teachers need to continue to develop the use of this combination of media in a more systematic Arabic learning plan.